Frontal Base Gliosarcoma Mimicking as Olfactory Groove Meningioma- A Rare Case Report (Bangladesh Journal of Neurosurgery, 2019)
Gliosarcoma is a rare tumour of the brain. It is a type of the gliobalstoma. This tumour has high complication rate as well as mortality. In our Institution, a 30 year old female was admitted with the complaints of headache and vomiting and weakness of rt. side of the body. She had history of radiotherapy on the frontal bone at four years age and following enucleation of the left eye. Now her recent MRI showed features of a tumor compatible with olfactory groove meningioma. She underwent craniotomy and her tumour was removed. Her histopathological exam was compatible with gliosarcoma which was confirmed with immunohistochemistry. And she was referred to oncologist for further management. Gliosarcoma is a rare intracranial tumour which has variable presentation. The aim of this case report is to present a secondary gliosarcoma which had presented as olfactory groove meningioma.Bang. J Neurosurgery 2019; 8(2): 108-111